Effects of Iliotibial Band Myofascial Release with/without Stretching with Iliotibial Band Tightness Secondary to Knee Osteoarthritis - Hamna Rahman, Zirwa Afzal, Osama Ramzan, Saman Tauseef, Tahreem Usman, Syeda Iqra Qadeer, Sania Maqbool (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Knee osteoarthritis (OA), also referred to as degenerative joint disease of the knee, is brought on by wear-and-tear and the slow loss of articular cartilage. The term "iliotibial band" (IT band) also refers to the iliotibial tract or Maissiat’s band. Methodology: This study was conducted using randomized clinical trial, quasi experimental research design as we need to make 2 groups and evaluate the effects of Iliotibial band myofascial release and stretching on the patients of knee OA. Study population was 36 individuals of ages 50-70 having knee osteoarthritis grade II or III characterized by Kellgren-Lawrence grades, visiting the physical therapy department of Mumtaz physiotherapy clinic. It was a randomized clinical trial with convenient sampling where participants were randomly allocated in two groups by simple random sampling, one group was experimental that received IT band myofascial release other than the stretching and baseline treatment and second group received the myofascial release and baseline treatment only. Data collection tools were Visual Analogue Scale (VAS) and Woman Osteoarthritis index. For the within group analysis of VAS, Friedman test was used and wilcoxon signed rank test was used for the within group analysis of the WOMAC. For the between group analysis of variables, Mann-whitney U test was used. Results: Both groups showed some significant improvement in all outcome measures (p<0.05), but the results produced by IT band Myofascial release along with stretching group was statistically significant in terms of reduced pain and disability (p<0.0005) as compared to myofascial release alone group. The iliotibial band myofascial release along with stretching has statistically significant effect in improving the pain and disability among knee osteoarthritis patients. Practical Implication: Iliotibial band tightness can potentially lead to the alterations in the mobility of patella and disturb the overall knee complex. Proper arthrokinematics of joint is necessary for ambulation. So, this study focused to draw results from combined therapy of IT band myofascial release and stretching will redound to the benefit of physiotherapy field considering that knee plays an important role in better Quality of life. Conclusions: The iliotibial band myofascial release along with stretching has statistically significant effect in improving the pain and disability among knee osteoarthritis patients. Keywords: IT Band; Myofascial Release; Stretching; WOMAC; VAS.